2011
DOI: 10.1093/treephys/tpr083
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of transcriptional and physiological responses to salinity stress in two contrasting Populus alba L. genotypes

Abstract: Soil salinity is an important limiting factor to tree growth and productivity. Populus alba L. is a moderately salt-tolerant species and its natural populations are adapted to contrasting environments, thus providing genetic resources to identify key genes for tolerance to abiotic stress, such as salinity. To elucidate the molecular and genetic basis of variation for salinity tolerance in P. alba, we analyzed the short-term ecophysiological and transcriptome response to salinity. Two contrasting genotypes, 6K3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 93 publications
0
24
0
1
Order By: Relevance
“…Moreover, an increase in Rubisco Activase was seen in our last experiment on cultivated barleys during salinity (Fatehi et al 2012a). Downregulation of rubisco activase was reported in sensitive plants under stress conditions (Sobhanian et al 2010;Beritognolo et al 2011). The increase in Rubisco Activase may result from their chaperon function that needs more study (Fatehi et al 2012a).…”
Section: Photosynthesis-related Proteinsmentioning
confidence: 99%
“…Moreover, an increase in Rubisco Activase was seen in our last experiment on cultivated barleys during salinity (Fatehi et al 2012a). Downregulation of rubisco activase was reported in sensitive plants under stress conditions (Sobhanian et al 2010;Beritognolo et al 2011). The increase in Rubisco Activase may result from their chaperon function that needs more study (Fatehi et al 2012a).…”
Section: Photosynthesis-related Proteinsmentioning
confidence: 99%
“…In the present study, the down-regulation of Hsps/chaperones (Spots 56, 57 and 59) indicates the protein denaturation and oxidative modifications may occur in VN cultivar by salt stress. Enhanced salt-induced expression of an HSP70 was shown to contribute to salinity tolerance in a tolerant poplar cultivar (Beritognolo et al, 2011). Postnikova et al (2013) reported the expression of HSP70 mRNA in AZ-88NDC alfalfa line.…”
Section: Protein Folding Turnover and Signalingmentioning
confidence: 99%
“…Of particular interest is isoprene, a hemiterpene that is known to behave as an antioxidant Loreto and Velikova, 2001;Calfapietra et al, 2008) and as a thylakoid membrane stabilizer that reduces the formation of ROS (Velikova et al, 2012), and whose indirect role in cooperating with nitric oxide (NO) and other reactive species in the installation of secondary signaling has also been suggested (Vickers et al, 2009a). In addition to acting as antioxidants, volatile isoprenoids are involved in a wide variety of plant responses to exogenous stimuli, conferring protection against high temperatures (Sharkey and Yeh, 2001;Sharkey et al, 2008;Rasulov et al, 2010), excessive light radiation (Loreto and Sharkey, 1990;Loreto et al, 2006), drought (Brilli et al, 2007;Michelozzi et al, 2011;Nogués et al, 2012), salt stress (Loreto and Delfine, 2000;Beritognolo et al, 2011), herbivores (Laothawornkitkul et al, 2008), and mechanical wounding (Brilli et al, , 2012, and also playing relevant roles in tritrophic interactions (Loivamäki et al, 2008).…”
mentioning
confidence: 99%